Payments for environmental services: some nuts and bolts - Wunder, Sven (2005)
Payments for environmental services (PES) are part of a new and more direct conservation paradigm, explicitly recognizing the need to bridge the interests of landowners and outsiders. Eloquent theoretical assessments have praised the absolute advantages of PES over traditional conservation approaches. Some pilot PES exist in the tropics, but many field practitioners and prospective service buyers and sellers remain skeptical about the concept. This paper aims to help demystify PES for non-economists, starting with a simple and coherent definition of the term. It then provides practical ‘how-to’ hints for PES design. It considers the likely niche for PES in the portfolio of conservation approaches. This assessment is based on a literature review, combined with field observations from research in Latin America and Asia. It concludes that service users will continue to drive PES, but their willingness to pay will only rise if schemes can demonstrate clear additionality vis-à-vis carefully established baselines, if trust-building processes with service providers are sustained, and PES recipients’ livelihood dynamics is better understood. PES best suits intermediate and/or projected threat scenarios, often in marginal lands with moderate conservation opportunity costs. People facing credible but medium-sized environmental degradation are more likely to become PES recipients than those living in relative harmony with Nature. The choice between PES cash and in-kind payments is highly context-dependent. Poor PES recipients are likely to gain from participation, though their access might be constrained and non-participating landless poor could lose out. PES is a highly promising conservation approach that can benefit buyers, sellers and improve the resource base, but it is unlikely to completely outstrip other conservation instruments.